POST-SOVIET ASIA: NEW GEOPOLITICAL TRENDS AND RUSSIA’S INTERESTS - GROZIN, Andrei (CENTRAL ASIA AND THE CAUCASUS, 2007)
Until the late 1999, post-Soviet Central Asia as a whole, with the exception of Tajikistan, was seen as a stable region not prone to conflicts. There was still no talk of another round of the Big Game that brought the leading world centers into the continent’s “heartland.” This talk began later, at the end of 2001. Today, we all know that the external stability of the 1990s was nothing but a shell filled with vast destructive potential. So far, the Central Asian republics have not yet identified their geopolitical vectors—too many countries with special interests are present in the region. This, together with the vast and varied raw material resources, has greatly increased the newly sovereign Central Asian countries’ geopolitical and geo-economic weight. In 2005-2006, “new Asia” attracted more attention from observers than the other post-Soviet regions. The Tulip Revolution in Kyrgyzstan, the Andijan events in Uzbekistan, and the presidential elections in Kazakhstan provided ample forecasting material. Today the Central Asian situation has become relatively stable, yet serious storms are still to come. Russia’s policy, although betraying new trends in this key region, remains vague. Today, however, Russia should acquire a new conception of its political and economic presence in Central Asia.